Parents’ Perceptions of the Development of Religious and Moral Values in a Parenting Program at TKK Negeri Bogenga: Persepsi Orang Tua terhadap Perkembangan Aspek Nilai Moral Agama Program Parenting Di TKK Negeri Bogenga - Maria Rosalia Ede; Gde Putu Arya Oka; Marsianus Meka; Efridai Ita (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
This study aims to explore parents' perceptions in supporting the development of moral and religious values ​​in early childhood through a parenting program at Bogenga State Kindergarten (TKK Negeri Bogenga). This research is important because the role of parents is crucial in determining the success of instilling character values ​​in children from an early age. The study used a qualitative approach with a descriptive phenomenological design. The research subjects consisted of three parents with children aged 5–6 years and were selected using a purposive sampling technique. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive analysis model of Matthew B. Miles, A. Michael Huberman, and Johnny Saldaña, which includes data reduction, data presentation, and drawing conclusions. The results showed that parents had a positive perception of the parenting program, especially through home visits and intensive communication with teachers. The parenting program has been proven to help parents in instill moral and religious values ​​through role models and habits at home. This research contributes to the development of sustainable parenting programs to strengthen partnerships between schools and families in the character development of early childhood.